2008
DOI: 10.1074/jbc.m806992200
|View full text |Cite
|
Sign up to set email alerts
|

A Disease-causing Point Mutation in Human Mitochondrial tRNAMet Results in tRNA Misfolding Leading to Defects in Translational Initiation and Elongation

Abstract: The mitochondrial tRNA genes are hot spots for mutations that lead to human disease. A single point mutation (T4409C) in the gene for human mitochondrial tRNA Met (hmtRNA Met ) has been found to cause mitochondrial myopathy. This mutation results in the replacement of U8 in hmtRNA Met with a C8. The hmtRNA Met serves both in translational initiation and elongation in human mitochondria making this tRNA of particular interest in mitochondrial protein synthesis. Here we show that the single 8U3 C mutation leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 53 publications
(62 reference statements)
0
33
0
Order By: Relevance
“…In this study, the primer extension experiment demonstrated that the m.7551A > G mutation produced the m 1 G37 modification of mt–tRNA Asp . The primary defect in this mutation appeared to affect the stability and aminoacylation of mutant mt–tRNA Asp (50,51). Unlike the m.12201T > C mutation in the mt–tRNA His and m.15927A > G mutation in the mt–tRNA Thr (20,50), the m.7551A > G mutation did not change conformation of mt–tRNA Asp .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the primer extension experiment demonstrated that the m.7551A > G mutation produced the m 1 G37 modification of mt–tRNA Asp . The primary defect in this mutation appeared to affect the stability and aminoacylation of mutant mt–tRNA Asp (50,51). Unlike the m.12201T > C mutation in the mt–tRNA His and m.15927A > G mutation in the mt–tRNA Thr (20,50), the m.7551A > G mutation did not change conformation of mt–tRNA Asp .…”
Section: Discussionmentioning
confidence: 99%
“…E. coli [ 14 C]Phe-tRNA and the human mitochondrial [ 35 S]Met-tRNA transcript were prepared as described [11,12]. Mitochondrial tRNA was purified from bovine mitoplasts using the Qiagen RNA/DNA maxi kit.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, mutations in mitochondrial tRNAs are implicated in human diseases (29), and such a mutation has been reported to result in tRNA misfolding (30). Similarly, mutations in cytoplasmic tRNA His lead to tRNA misfolding and in turn reduced processing of precursor tRNAs (31).…”
Section: Discussionmentioning
confidence: 99%